Strategies to improve the adolescent’s reproductive health knowledge in the traditional Islamic Boarding School in Sidoarjo, Indonesia - Rize Budi Amalia; Ivon Diah Wittiarika; Ratna Dwi Jayanti (Journal of Midwifery, 2020)
Adolescence is an important stage the girl’s life which the crucial developmental reproductive such as menstruation and pubertal occur. The peer nowadays has a crucial role in determining the proper health reproductive knowledge due to the lack of information from the family and education system. This study aimed to observe the effectiveness of the trained peer educator compared to the expert educator in delivering reproductive health knowledge. The study was using pre - and post - intervention (quasi - experimental) design. The sample taken by random sampling with the pretest and posttest questionnaire was applied to 98 female students aged 12 to 15 at traditional Islamic boarding school in Sidoarjo, East Java. The participants consisting of 49 students were exposed by the trained peer educator compare to 49 students in which exposed by expert.  Wilcoxon Signed Rank Test indicated the significant difference between pretest-posttest in the group were exposed by the trained peer compared by the expert (p=0,001). The Mann Whitney Test indicate there was no significant difference of reproductive health knowledge (p=0,718) between posttest between two groups. In conclusion, the information given by the trained peer educator as effective as the information given by the expert and significantly improved the adolescents' reproductive health knowledge. Therefore, designing the trained peer approach to increase adolescent reproductive health is effective to structure.